Dynamics of medal shares at the IAAF World Championships athletics - a statistical analysis - Soulas, D.; Tsiokanos, A.; Voutselas, V.; Dick, F. (New Studies in Athletics, 2013)
Sport is a social phenomenon in which performances and high achievement reflect the overall achievements of a society. The aim of this study was to make a longitudinal analysis of high achievement in athletics, expressed in medals won at the IAAF World Championships in Athletics, in order to provide a basis for future work to better understand the factors that contribute to national sporting success and to help develop elite sport training and support systems. The medals won by all countries that participated in the championships from 1983 to 2011 were grouped by continent, gender and type of medal (gold, silver, bronze) and descriptive statistics was conducted. These are detailed in individual sections for each continent. Among the findings are that the combined men`s and women`s shares of the total medals won by continent are: Europe 50.85%, the Americas 29%, Africa 13.57%, Asia 4.71% and Oceania to 1.87%. However, between the 1983 and 2011 editions of the championships there was a significant decline in Europe`s share, which is offset by increases mainly from the America`s and Africa. The authors conclude with a recommendation for deeper and multidisciplinary analysis of all the trends identified.